POTENTIAL ROLE OF SERUM PERIOSTIN IN THE EARLY DETECTION OF BRONCHIAL ASTHMA IN CHILDREN - Nickolai V. Sobotyuk; Valentina P. Gaponenko; Sergei V. Bochantsev; Svetlana A. Golochalova; Irina V. Sazonova; Tatiana N. Кharlamova (Вопросы современной педиатрии)
Respiratory viral infections in infants and preschool children are often accompanied by repeated episodes of wheezing; which is associated with an increased risk of asthma development. Mechanisms of connection between a viral infection and the subsequent development of allergic inflammation in the respiratory tract are insufficiently studied. Unfortunately; despite the existence of such connection; it is difficult to predict the risk occurrence on the basis of clinical symptoms. Determination of nitrogen oxide in the exhaled air; of the number of eosinophils in the peripheral blood and of bronchoalveolar lavage fluid as well as of IgE was suggested as predictors of allergic inflammation in the airways. But these surrogate markers in patients including children with asthma have a moderate diagnostic accuracy. Their use as a marker of airway eosinophilia can cause a significant amount of false-positive and false-negative results. Recent studies have shown that determination of serum periostin more accurately confirms eosinophilic airway inflammation. The possibility to study this marker in different variants of wheezing in children as a possible predictor of asthma development is discussed based on its reliability; stability and a small variation in determination of eosinophilic inflammation in the airways with symptoms of bronchial obstruction.